Europe and empire : on the political forms of globalization - Cacciari, Massimo (Commonalities., 2016)
"Assesses the current situation of Europe ten years after the adoption of the single currency. Examines the genealogy of the idea of Europe from the Greek confrontation with the Asia to the conflict between the Roman Empire and Christianity. Discusses the role of secularization in the shaping of modern Europe"--